Widening Cross-border Participation: Building ODL Communities Through Internationalisation at Open University Malaysia - Santhi , Raghavan (Open University Malaysia (OUM), 2009)
With the new challenges of a global knowledge-based economy, it is essential to strengthen a nation’s workforce. A knowledgeable, productive and competent workforce is a pre-requisite for the elevation of the country’s human resources in order to meet the challenges of information and communication technology and knowledge explosions. Continuous upgrading through education and training guarantees the successful development of the workforce and the nation’s knowledge-based economy in a global environment. Flexibility and accessibility of technology-based learning simplifies cross-border education among countries. Learning has now become mobile and more accessible, at a reasonable cost. This paper reports how Open University Malaysia (OUM) employs open and distance learning (ODL) as an approach to provide and expand education, capacity building and human resource development opportunities through cross-border education. This paper has resulted in additional insight relating to the effectiveness of the ODL techniques used. It analyses OUM’s networking strategies and collaborative efforts from an international perspective. (Authors' abstract)